Das Malerische and the Picturesque: Seeing Architecture in Translation. Issue 1 (9th May 2019) - Macarthur, John; Aitchison, Mathew; Cepl, Jasper
Abstract : Picturesque is a term which owes part of its historical success to its ambiguity, signifying both an origin of subjectivist aesthetics and a popular naïve taste for the rustic. For historians of art and architecture this ambiguity is ramified by an issue of translation between 'picturesque' and its usual equivalent in German, malerisch . In Heinrich Wölfflin's influential account of the history of art since the Renaissance, Kunstgeschichtliche Grundbegriffe (1915 ), he systematized das Malerische as a formal value in dialectic with 'the linear'. He defined the art historical malerisch by contrasting it with the belief of naïve observers that picturesqueness was a property of objects. These two inflections of picturesque already existed in English usage, but to make them clearer, translations of Wölfflin since 1932 have rendered the more complex use of malerisch through the neologism 'painterly'. Other historians did not accept the neologism. In particular, Nikolaus Pevsner, imbued with the German tradition, wrote in his English language texts of the malerisch qualities of architecture and urbanism as 'picturesque'. Thus, a level of confusion has resulted in distinguishing 'painterly' and 'picturesque', as if there was a conceptual difference marked in everyday language, rather than a difference constructed by the institutions of art history. Translations, and particularly those that make common words into defined terms, are valuable points of historical enquiry in their own right. At such points we can recover some of the complexity and historical density that has been lost in the schematisation that has come about through translation.